(untitled) (Terr@ Plural, 2019)
This paper aimed to analyse the process of urban verticalization in the main morphologies of the process and to identify the main producers of urban verticalization in a Brazilian medium-sized city. Through the analytical categories of space discussed by Milton Santos and field incursions, it was observed that the privileged form of the urban verticalization process was the four-floor building inside condominiums produced by a group quite specific of companies operating on a regional and national scale.